Innovation in craftsmanship family Smes in times of digitalization - Überbacher, Ruth; Brozzi, Riccardo; Matt, Dominik Tobias (Piccola Impresa / Small Business, 2020)
Digital Transformation is radically changing the concept of production and the dynamics among producers, suppliers and end-users in companies across several sectors. Besides large companies, also Small and Medium sized Enterprises (SMEs) operating in the craftsmanship industry currently witnesses a fundamental transition toward the digital paradigm. Particularly in Italy such craftsmanship SMEs are mostly family-managed and family-owned. Due to their peculiar characteristics, family SMEs find themselves under severe innovation pressure in times of digitalization. This study set out to investigate the digital present and future expected level of craftsmanship family SMEs in the Italian northernmost Region of South-Tyrol. Through an online self-assessment tool (DigiCheck), data from 100 South Tyrolean craftsmanship family SMEs were collected. The study offered insights into the attitude of companies towards digitalization, the opportunities but also the challenges they face currently and in the future. Furthermore, based on the digitalization level of companies, four taxonomies of digital family SMEs were derived: Digital Leader, Digital Motivator, Digital Follower, Digital Steady-State. The results indicate a relatively high willingness to innovate towards Industry 4.0, however major challenges hampering family SMEs of the craftsmanship sector adopting new technologies and introducing digital solutions need to be tackled